Evaluasi Konstanta Kecepatan Ekstraksi Beta (ß)-Karoten Berbasis Campuran Pelarut Aseton dan Dietil Eter - Johar, Nirmala; Mustikaningrum, Mega (Politeknik ATI Padang, 2023)
Research on the extraction of ß-carotene has been carried out intensively in recent years, considering the wide application of ß-carotene compounds, especially in the pharmaceutical and health fields. In the health sector, βcarotene has antioxidant compounds that can neutralize unstable molecules called free radicals. When the number of free radicals is too high in the body, it can cause cell and tissue damage which is known as oxidative stress. So the consumption of β-carotene should be increased. Various technologies are used for the isolation of ß-carotene from raw materials, such as maceration, soxhlet, ultrasound-assisted extraction (UAE), pressurized liquid extraction (PLE) and supercritical liquid extraction (SFE). This study uses the maceration method with the consideration that the energy used is relatively low and refers to the heat-resistant nature of β-carotene. The purpose of this study was to analyze the addition of co-solvent diethyl ether to acetone solvent to the value of the extraction rate constant (k). In this case, the addition of a co-solvent can help transport β-carotene to the solvent effectively by increasing the yield of β-carotene produced. Quantitative analysis was carried out using calculations based on mass balance, pseudo- second-order, and Peleg to then conclude which model is by the resulting data. The final yield of β-carotene was 34.395; 103.287 and 108.974 µg/g for diethyl ether, acetone, and a mixture of acetone with diethyl ether (24: 1) v/v respectively. The value of the extraction speed constant for each solvent diethyl ether, acetone, and a mixture of acetone with diethyl ether was 0.8913; 1.03975, and 2.0975 (minute-1) based on the Peleg model and 0.00738 for each solvent; 0.00828; 0.0141 (gram/mg.minute) based on the pseudo second-order model.